227 Dysautonomia in children with irritable bowel syndrome and inflammatory bowel disease. (11th October 2021) - Geljic, Antonella; Junakovic, Anamari; Trivic, Ivana; Sila, Sara; Skoric, Magdalena Krbot; Habek, Mario; Hojsak, Iva
Abstract : To evaluate the presence of autonomic nervous system abnormalities (ANS) in children with irritable bowel syndrome (IBS) and quiescence inflammatory bowel disease (IBD) comparing to controls. Consecutive children with quiescence IBD, IBS and aged and sex matched healthy controls (HC) were referred for the evaluation of dysautonomia (IBD: N=24, mean age 15.7 yrs, 16 females; IBS: N=18, mean age 14.8 yrs, 9 females; HC: N=18, mean age 14.2 yrs, 9 females). Dysautonomia was evaluated subjectively with the Composite Autonomic Symptom Score (COMPASS 31), and objectively with the following autonomic tests: heart rate (HR) and blood pressure (BP) responses to the Valsalva maneuver, heart rate response to deep breathing (RSA), blood pressure response to passive tilt, and quantitative sudomotor axon reflex test (QSART). Additionally, heart rate variability (HRV) analysis was performed by Kubios HRV 2.2. Following HRV parameters were compared between the groups in supine and tilted positions: total power of low (LF) and high frequency domain components (HF), normalized HF (HFnu), low-to-high frequency ratio (LF/HF), standard deviation of normal-to-normal intervals (SDNN) and percentage of successive RR intervals that differ by more than 50 ms (PNN50). Children with IBS scored highest on COMPASS-31, followed by patients with IBD and HC (median 15.6, 8.7 and 2.3, respectively, p<0.001). Similar differences were observed in the orthostatic intolerance and gastrointestinal domains of the COMPASS-31. No differences between groups were observed in HR and BP responses to the Valsalva maneuver, RSA and BP response to passive tilt. Children with IBS had higher sweat volumes on proximal lower leg on QSART (median IBD 0.9, IBS 1.5, HC 0.8 µL; p=0.039). There was no difference in the HRV parameters between groups. However, children with IBS had significantly higher drop in LF (p=0.01) and SDNN (p=0.03) and lowest drop in PNN50 (p=0.01) during tilt test compared to children with IBD and HC. We found significant subjective and objective ANS abnormalities in children with IBS compared to children with IBD and HC.